SORPTION PROPERTIES OF PERIODATE OXIDIZED COTTON - Tanja Nikolić; Mirjana Kostić; Jovana Praskalo; Živomir Petronijević; Petar Škundrić (Chemical Industry and Chemical Engineering Quarterly, 2011)
The effect of periodate oxidation on the chemical and sorption properties of cotton yarn was investigated by determining aldehyde group content, moisture sorption, water retention and iodine sorption. Oxidation of cotton yarn was performed by varying concentration of sodium periodate solution and reaction time. To measure the aldehyde content present in the oxidized cotton, the aldehyde groups were selectively oxidized to carboxyl groups with sodium chlorite at pH 4-5, at room temperature for 48 h, and carboxyl group content was determined by modified calcium-acetate method. Differences in the sorption properties of untreated and oxidized cotton samples were obtained using conventional methods. The aldehyde groups were introduced into the oxidized cotton up to 99.2 µmol/g. Compared to the untreated fibers, oxidized cotton samples exhibited higher moisture sorption (up to 9%) and lower water retention values (up to 19%) and iodine sorption values (up to 31%). Based on the obtained results, it can be concluded that the crystalline structure of cellulose is not significantly changed by periodate oxidation, which is of great importance for textile material production.